2021
DOI: 10.1002/pros.24144
|View full text |Cite
|
Sign up to set email alerts
|

Inverse agonism at the Na/K‐ATPase receptor reverses EMT in prostate cancer cells

Abstract: The surface expression of Na/K-ATPase α1 (NKA) is significantly reduced in primary prostate tumors and further decreased in bone metastatic lesions. Here, we show that the loss of cell surface expression of NKA induces epithelial-mesenchymal transition (EMT) and promotes metastatic potential and tumor growth of prostate cancer (PCa) by decreasing the expression of E-cadherin and increasing c-Myc expression via the activation of Src/FAK pathways. Mechanistically, reduced surface expression of NKA in PCa is due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…One important step in the process is the infiltration of tumor cells into the circulatory system through the basement membrane, and EMT plays a key role in this metastasis cascade reaction. EMT causes tumor cells to lose epithelial-like polarity and acquire mesenchymal characteristics, thereby increasing the metastatic and invasive potential of the cells [ 16 ]. EMT promotes tumor metastasis by upregulating or downregulating the expression of epithelial markers such as MMP-2, MMP-9, VEGF, vimentin, E-cad, and N-cad [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…One important step in the process is the infiltration of tumor cells into the circulatory system through the basement membrane, and EMT plays a key role in this metastasis cascade reaction. EMT causes tumor cells to lose epithelial-like polarity and acquire mesenchymal characteristics, thereby increasing the metastatic and invasive potential of the cells [ 16 ]. EMT promotes tumor metastasis by upregulating or downregulating the expression of epithelial markers such as MMP-2, MMP-9, VEGF, vimentin, E-cad, and N-cad [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it also triggers a metabolic switch from mitochondrial oxidative phosphorylation to aerobic glycolysis (Warburg effect) [103]. Reduced alpha 1 NKA expression and subsequent Src/FAK pathway activation enhances prostate cancer metastatic potential, through decreased E-cadherin and increased c-myc expression [104].…”
Section: P-class Pumpsmentioning
confidence: 99%
“…For instance, 2D cells are stretched out on a flat substrate, while 3D cells on a natural or synthetic scaffold material maintain normal morphology and multiple contacts with the surrounding cells, and these differences in the morphological spread contribute to the differences in the drug response between the two. Moreover, the difference in the expression and the spatial organization of surface receptors in these two models also affects the response to drugs since the levels of receptors and the binding efficiency of a drug to these receptors is different due to the difference in the structure, localization, and spatial organization of these receptors on cell surfaces [ 93 , 94 ]. In addition, there is a difference in cancer gene expression levels because in 2D cell culture, some genes are differently expressed, which can lead to the different response and, thus, affect the effectiveness of a drug [ 93 , 95 ].…”
Section: Three-dimensional Prostate Cancer Models In Drug Discoverymentioning
confidence: 99%